Effect of accelerated feeding in the growth performance and carcass quality in native kids - T.Muthuramalingam; E. Rachel Jemimah; P.Tensingh Gnanaraj; P. Pothiappan; A. Shanmuga sundaram (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A trial was conducted to evaluate the effect of accelerated feeding method in the growth and carcass studies of native goat kids. Thirty male country goat (non – descriptive) kids at the age of 30 - 45 days were selected for this study. The kids were divided into two groups, control and treatment groups, each consist of 15 kids. The control group kids were fed with concentrate feed consisting of 15% crude Protein (CP), 75% Total Digestible Nutrient (TDN), CO4 grass as a sole green fodder and sorghum stover, bengal gram and groundnut tops as a dry fodder. The treatment group kids were fed with concentrate feed containing 21% crude Protein (CP), 75% Total Digestible Nutrient (TDN), CO4 grass and COFS 29 grass as a green fodder and sorghum stover, bengal gram and groundnut tops as a dry fodder. In addition the treatment group kids were fed with supplements such as TANUVAS mineral mixture, probiotics, baking soda and Groviplex®, Ostovet®, Brotone®. The study was conducted for a period of 6 months. The body weight of kids was recorded at fortnight intervals. Parameters such as average feed intake per goat, average total body weight gain, average daily body weight gain and cost of production per kg live weight gain were studied. The kids were slaughtered at the end of study period and carcass parameters like pre slaughter weight, carcass weight, dressed weight and weights of blood, head, feet, stomach with contents, lungs, heart, kidney, spleen, liver and skin were studied. After analysis of data, significant (P< 0.01) difference was noticed between control group and treatment group in terms of final body weight (C -13.28±0.10 kg, T - 17.00±0.06 kg), average total body weight gain (C -6.74 ±0.09 kg, T - 9.98±0.10 kg), average daily body weight gain (P< 0.05) (C - 0.04±0.08 kg, T - 0.06±0.09 kg) and cost of production per kg live weight gain (C– Rs.98.15±0.15, T – Rs.72.48±0.12) . There was also highly significant difference (P < 0.01) was noticed in carcass quality in terms of pre slaughter weight (C -13.28±0.10 kg, T - 17.00±0.06 kg), carcass weight (C - 6.25±0.10kg, T - 8.00±0.02 kg), dressed weight (C -5.70±0.15 kg, T - 7.55±0.14 kg), dressing percentage (C - 42.22±0.13%, T - 47.06±0.12%), head (C - 1.13±0.22 kg, T - 1.25±0.02 kg) and stomach (C - 5.10±0.26 kg, T - 6.35±0.2kg). Thus it is concluded that, accelerated feeding significantly improves the body weight gain and carcass yield in native goat kids with low production cost per kg live weight gain.